Marketing communication in the light of challenges brought about by virtualisation and interactivity - Mazurek-Łopacińska, Krystyna; Sobocińska, Magdalena (Economics and Business Review, 2016)
The development of marketing communication is multi-directional and itsnew dimensions and forms are related to new business ideas, the growing use of theInternet and the changing behaviour of media users. The article aims to show the mainchanges in the field of marketing communication which are expressed through thegrowing influence of the new media, the development and increasingly professionalcharacter of marketing communication, both at the stage of ideas and forms, as wellas the organisation of communication actions by enterprises and other entities on themarket. This is tied to the changing role of the consumer in the marketing communicationprocess and their increased activity at all stages of the value management process.Amongst the directions of marketing communication development and its increasinglyinternational and professional character – as manifested by various entities with a bigpotential to advance creative businesses – should be noted as well. Moreover an intertwiningof marketing communication with pop culture is observable. The changes inmarketing communication presented in this article imply a new set of challenges formarketing research. The article is based on a literature review and an analysis of selectedresults of quantitative research conducted as part of the Internet in marketingand the use of new technologies in cooperation between a firm and its clients project.